To simplify the expression 3/10x + 1/6y + 3/10x + 3/6y, we can combine like terms.
The terms 3/10x and 3/10x have the same coefficient of 3/10, so we can combine them by adding their constants together: 3/10x + 3/10x = (3/10 + 3/10)x = 6/10x = 3/5x.
Similarly, the terms 1/6y and 3/6y have the same coefficient of 1/6, so we can combine them by adding their constants together: 1/6y + 3/6y = (1/6 + 3/6)y = 4/6y = 2/3y.
Therefore, the simplified expression is 3/5x + 2/3y.
Simplify 3/10x + 1/6y + 3/10x + 3/6y . Be sure to reduce any fractions to the lowest terms.(1 point)
1 answer